2018
DOI: 10.1093/dnares/dsy029
|View full text |Cite
|
Sign up to set email alerts
|

ARIADNA: machine learning method for ancient DNA variant discovery

Abstract: Ancient DNA (aDNA) studies often rely on standard methods of mutation calling, optimized for high-quality contemporary DNA but not for excessive contamination, time- or environment-related damage of aDNA. In the absence of validated datasets and despite showing extreme sensitivity to aDNA quality, these methods have been used in many published studies, sometimes with additions of arbitrary filters or modifications, designed to overcome aDNA degradation and contamination problems. The general lack of best pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Studies of aDNA often use methods designed for contemporary data for variant calling, which can lead to inaccurate results ( 55 ). ( 32 ) performed a genomic analysis of individuals who lived around 3200 BCE and part of this was an HLA analysis of 23 individuals where they observed notable shifts in allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of aDNA often use methods designed for contemporary data for variant calling, which can lead to inaccurate results ( 55 ). ( 32 ) performed a genomic analysis of individuals who lived around 3200 BCE and part of this was an HLA analysis of 23 individuals where they observed notable shifts in allele frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of aDNA often use methods designed for contemporary data for variant calling, which can lead to inaccurate results (50). (25) performed a genomic analysis of individuals who lived around 3200BCE and part of this was an HLA analysis of 23 individuals where they observed some “striking shifts in allele frequencies”.…”
Section: Discussionmentioning
confidence: 99%
“…However, these limitations should not be used as a scapegoat to justify scientific lagging in our field, as methods tailored for aDNA analysis do exist. For example, damage-aware variant callers (e.g., snpAD [ 51 ], AntCaller [ 52 ], and ARIADNA [ 53 ]) have been developed, primarily for human population genomics, but could also potentially be tested for metagenomic contexts. Hence, it is very important that we do spend the appropriate amount of time and energy on validating our analyses to show that they do not suffer from biases introduced by unfit methods and on developing tailored software when necessary (examples of existing benchmarking studies, software, and pipelines can be found in Table 2 ).…”
Section: Considerations For Data Analysismentioning
confidence: 99%